Penataan Organisasi Pusat Pengembangan Sumber Daya Manusia Aparatur Melalui Revisi Peraturan Menteri ESDM No. 13 Tahun 2016 - Aulia Rakhman, Fahmi; Anggarini, Dian (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2019)
This research is focused on describing the need for reorganization in the Human Resources Development Center for Government Apparatus (PPSDMA) due to the need for simplication and synchronization between activities. The method used in this study is a qualitative method. This research was proposed to analyze and reveal the ineffectiveness in organizational functions and the overlapping authority in the organization of the the Human Resources Development Center for Government Apparatus (PPSDMA). The results of this paper illustrate that there are signicant changes in the duties and functions of the eldin PPSDMA based on the Minister of Energy and Mineral Resources Regulation No. 13 of 2016 compared to the proposed reorganization. ABSTRAKPenelitian ini difokuskan untuk mendeskripsikan perlunya reorganisasi di Pusat Pengembangan Sumber Daya Manusia Aparatur (PPSDMA) dikarenakan perlunya simplikasi dan sinkronisasi antar kegiatan. Metode yang digunakan dalam penelitian ini yaitu metode kualitatif. Penelitian ini diajukan untuk menganalisis dan mengungkapkan ketidakefektifan dalam fungsi organisasi dan adanya tumpang tindihkewenangan di organisasi Pusat Pengembangan Sumber Daya Manusia Aparatur. Hasil dari penulisan ini menggambarkan adanya perubahan signikan dari tugas dan fungsi bidang di PPSDMA berdasarkan Peraturan Menteri ESDM Nomor 13 Tahun 2016 berbanding dengan usulan reorganisasi.